INSTITUTIONAL BASIS OF UKRAINE’S ECONOMIC SECURITY - Odnostalko , D. (Theory and Practice of Public Administration, 2021)
The article analyzes the competencies of state institutions to ensure the economic security of Ukraine, based on indicators of its assessment. It is established that the policy of ensuring economic security in the country and the choice of appropriate strategy is carried out by the highest state authorities - the President of Ukraine, the Verkhovna Rada of Ukraine, the Cabinet of Ministers of Ukraine. It is noted that the institutional basis for ensuring economic security should be the activities of state authorities that have the appropriate powers in different areas and in different areas. At the same time, economic security should be considered on the one hand as a component, on the other - as the basis of national security of the state as a whole. The definition of the tasks of the authorities to ensure economic security should be based on the mutual influence of the three areas, which should include financial, humanitarian and purely economic. However, it should be borne in mind that it is not possible to clearly delineate the limits of the authorities’ competence with respect to each of the components of economic security, which is entirely justified because they are interrelated and interdependent. Authorities, comprehensively performing the functions established by law, should be responsible for compliance with norms and indicators that are indicators of the assessment of economic security of the state. The article proves the expediency of introducing a state institution in Ukraine, the tasks of which would be to coordinate the activities of public authorities to ensure the economic security of the state, development of recommendations and proposals for strategic objectives of the state in the field of economic security.